2005
DOI: 10.1108/13660750510611189
|View full text |Cite
|
Sign up to set email alerts
|

A survey of total quality management in Iran

Abstract: Purpose-The objective of this research is to investigate the success of TQM and barriers to its successful implementation in health care services organizations in Isfahan province, Iran, 2004. Design/methodology/approach-This descriptive and cross-sectional research was done via two questionnaires (TQM success and its barriers). The statistical population of this research consists of all managers of health care services organizations who implemented TQM in their organizations (90 managers). Findings-TQM succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 86 publications
5
29
0
Order By: Relevance
“…This result is consistent with previous studies (Desai, 2010;Karaszewski, 2004;Rad, 2005), which found lack of training as a QMS obstacle in some hospitals. This finding indicates that perhaps low-performing hospitals in Jordan, which are mainly public hospitals are not providing enough in-service training programmes to their staff due to declining government spending on health (Jordanian Department of Statistics (JDOS), 2010; Jordanian High Health Council, 2012).…”
Section: Major Qms Obstacles In High-and Low-performing Hospitalssupporting
confidence: 93%
See 4 more Smart Citations
“…This result is consistent with previous studies (Desai, 2010;Karaszewski, 2004;Rad, 2005), which found lack of training as a QMS obstacle in some hospitals. This finding indicates that perhaps low-performing hospitals in Jordan, which are mainly public hospitals are not providing enough in-service training programmes to their staff due to declining government spending on health (Jordanian Department of Statistics (JDOS), 2010; Jordanian High Health Council, 2012).…”
Section: Major Qms Obstacles In High-and Low-performing Hospitalssupporting
confidence: 93%
“…This result is consistent with other studies conducted in different countries (Hudelson et al, 2008;Pongpirul et al, 2006;Rad, 2005). Inadequacy of staff was ranked as a major obstacle to QMS in hospitals based on health care professionals' views (Pongpirul et al, 2006).…”
Section: Major Qms Obstacles In High-and Low-performing Hospitalssupporting
confidence: 91%
See 3 more Smart Citations